Implementasi Model ESQ Pada Pendidikan Agama Islam di SDN 2 Kepanjen Malang - Peni Catur Ningtiyas (Institut Agama Islam Tribakti Kediri, 2020)
The nature of postmodernism thinking teaches to review educational concepts that have been considered standard. One of them is whether enough people are only emphasized to have intellectual intelligence alone? Departing from the questions above, this research was conducted using a library study approach. Literature study is a data collection technique by conducting a study of books, literature, notes, and reports that have to do with problems that are solved. From the results of this study, there are many different kinds of intelligence that are considered more important for life. Humans can be considered more chairy if they have some kind of intelligence, which consists of IQ (Intelligence Quotient), EQ (Emotional Quotient), SQ (Spiritual Quotient) and intelligence that Emotional spiritual quostient (ESQ) plays a crucial role in educational institutions that have Islamic base is able to develop Islamic education in Indonesia. The concept can be developed as follows: the concept of freedom of heart, the pillars of faith, the pillars of Islam, and monotheism. [Alam berfikir postmodernisme mengajarkan untuk meninjau ulang konsep-konsep pendidikan yang selama ini dianggap baku. Salah satunya adalah apakah cukup manusia hanya ditekankan untuk memiliki kecerdasan intelektual semata? Berangkat dari pertanyaan di atas, penelitian ini dilakukan dengan menggunakan pendekatan studi kepustakaan atau Library Research. Studi kepustakaan adalah teknik pengum-pulan data dengan mengadakan studi penelaahan terhadap buku-buku, literatur-literatur, catatan-catatan, dan laporan-laporan yang ada hubungannya dengan ma-salah yang dipecahkan. Dari hasil kajian ini, banyak ditemukan ragam kecerdasan yang justru lebih dianggap penting bagi kehidupan. Manusia bisa dianggap lebih kursial jika memiliki beberapa macam kecerdasan, yang diantaranya terdiri IQ (Intelegence Quotient), EQ (Emosional Quotient), SQ (Spiritual Quotient) dan kecerdasan yang Emotional spiritual quostient (ESQ) berperan krusial pada lembaga-lembaga pendidikan yang ber-basis Islam mampu mengembangkan pen-didikan Islam di Indonsia. Konsep yang bisa dikembangkan sebagai berikut: konsep kebebasan hati, rukun iman, rukun Islam, dan ketauhidan]